Flexible Thin Battery with Fast and Sensitive Voltage Control by a Simple Mechanical Bending: No Energy without Working - Hendry Izaac Elim; Meilladelfia Rahman; Wanda Sari Latupoho; Randy Rasyid Latuconsina; Aprilia Angel Pattipeilohy; M. V. Reddy; Rajan Jose (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
The competition among scientists in providing the best need of mobile energy in society has been spread worldwide. This short communication shares a newly simple invention about thin battery with its voltage control simply adjusted by bending it. The changing in battery voltage is quite fast only in few seconds and very sensitive according to the mechanical bending treated into it. Furthermore, the thin battery was fabricated to be water resistant so that it can be applied under water with special technology purposes. This invention is a new beginning for flexible thin battery (FTB) technology which can be implemented in many different activities of daily life such as integrated technology use, medical energy supports, and education smart tools.